Can autologous stem cell transplantation be a treatment option in a patient diagnosed with secondary progressive multiple sclerosis?:Case report - Kemal Fıdan; Gülşah Akyol; Ali Ünal (Hematology, Transfusion and Cell Therapy, 2024)
Case report: İntroduction: Multiple sclerosis (MS) manifests itself with plaque formation as a result of defensive T and B cells in the immune system perceiving the myelin sheath around nerve cells as a foreign substance to the body and trying to destroy it, for an unknown reason.In short, it is an autoimmune inflammatory demyelinating disease of the central nervous system.In multiple sclerosis, various interventions such as medication, physical therapy, and stem cell therapy are used to improve patients' quality of life. The goal of autologous hematopoietic stem cell transplantation (AHSCT) is to eliminate and replace the patient's pathogenic immune system to achieve long-term remission of MS.Here, we will present our experience with autologous stem cell transplantation performed in our center for an MS case that had previously received both medical and physical therapy and failed to respond.Key words: multiple sclerosis, autologous stem cell transplantation Case report: The 41-year-old male patient was diagnosed with MS in 2012 and has been wheelchair-bound for about 3 years. Glatiramer acetate was started at the time of diagnosis. As the patient's complaints increased, fampridine and ocrelizumab treatments were given, respectively. The patient, who did not respond to treatment, was evaluated as having secondary progressive MS and an autologous stem cell transplant was planned. Mobilization was performed with cyclophosphamide + G-CSF in July 2023. In September 2023, AHSCT was performed with cyclophosphamide (40 mg/kg, 2400 mg in total, 5 days), Mesna (40 mg/kg/day, 2400 mg in total, 5 days) and ATG (360 mg in total) protocol. The patient, who had platelet engraftment on day +9 and neutrophil engraftment on day +11 after AHSCT, was discharged with outpatient clinic control. Discussion and conclusion: Despite many advances in MS treatment, there is still no definitive treatment answer. Autologous hematopoietic stem cell transplantation may be promising, as observed in several studies. The aim of AHSCT is to eliminate and replace the patient's pathogenic immune system to ensure long-term remission of MS (1).In the MIST study; One group of patients with relapse-refractory MS (RRMS) underwent myeloablative AHSCT with cyclophosphamide (200 mg/kg) and antithymocyte globulin (ATG), and the other group was given disease-modifying therapy. During an average follow-up of 2 years, disease progression was 5% in the AHSCT group and 62% in the other group. In addition, those who underwent AHSCT had fewer relapses, and the rate of lesion healing on MRI was observed to be higher in the AHSCT group (2). In the HALT-MS study, event-free survival and improvement in neurological functions were observed at higher rates in patients who underwent AHSCT after high-dose immunotherapy (3-4). In a study conducted in Sweden, no recurrence or progression was observed in the first 3 years of treatment after AHSCT, and it was also stated that no new lesions developed on MRI (5).Although studies show the potential benefits of AHSCT, more long-term data from randomized controlled trials are needed to evaluate the effectiveness and safety of this intervention in the treatment of RRMS.